Analyzing Sharia Compliance in Fintech: Measuring the Relevance of its Services with the Principles of Islamic Economic Law - Risnawati, Nor; Fayyadhi, Weldy Ahmad (Jurnal Ar-Ribh, 2024)
This research is a literature review. The method used in this research is Library Research or literature review, which gathers data from literature and other sources that support and are relevant to the discussion in this research. The results of this research are that Fintech that adheres to Sharia principles has significant relevance in the context of Indonesia, where the majority of the population is Muslim. The practice of Fintech in accordance with Sharia economics reflects a commitment to avoiding usury, adhering to principles of Sharia financing, increasing consumer awareness, and supporting the growth of Sharia financial markets. This creates important economic, financial, and social benefits for the Muslim community while simultaneously reflecting values of integrity, transparency, and justice in business operations. Thus, this research emphasizes that the implementation of Sharia principles in Fintech is a wise and sustainable step in supporting the development of Islamic economics and financial services in line with Islamic values in Indonesia.Keywords: Islamic Economic Law, Fintech, Sharia Services